Modelling Free Flow Speed on Two-Lane Rural Highways in Bosnia and Herzegovina - Lovrić, Ivan; Cvitanić, Dražen; Breški, Deana (Promet - Traffic&Transportation, 2014)
Free flow speed is used as a parameter in transportation planning and capacity analysis models, as well as speed-flow diagrams. Many of these models suggest estimating free flow speed according to measurements from similar highways, which is not a practical method for use in B&H. This paper first discusses problems with using these methodologies in conditions prevailing in B&H and then presents a free flow speed evaluation model developed from a comprehensive field survey conducted on nine homogeneous sections of state and regional roads.